Influence of dimensional static and dynamic charges on conduction in the active zone of a quantum cascade laser - Gryschuk, A.M.; Boyko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The theory of active dynamic conductivity in the three-barrier active zone of a quantum cascade laser has been developed in the model of the electron effective mass and rectangular potential in the low signal approximation. In the preceding paper, it was shown that the static charge causes an increase of the lifetime of electronic quasistationary states and the shift of the energy levels into the high-energy range without changing maximum values of the active dynamic conductivity. The dynamic charge causes redistribution of the partial components of the active dynamic conductivity without affecting the spectral parameters of electron. It has been set that the partial components of the dynamic conductivity caused by the passing through electron flow from nanostructures reduce, and the components of conductivity caused by the flow in the opposite direction increase, thus, the conductivity value remains constant.